2021
DOI: 10.1038/s41398-021-01534-0
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances are associated with cortical and subcortical atrophy in alcohol use disorder

Abstract: Sleep disturbances are prominent in patients with alcohol use disorder (AUD) and predict relapse. So far, the mechanisms underlying sleep disruptions in AUD are poorly understood. Because sleep-related regions vastly overlap with regions, where patients with AUD showed pronounced grey matter (GM) reduction; we hypothesized that GM structure could contribute to sleep disturbances associated with chronic alcohol use. We combined sleep EEG recording and high-resolution structural brain imaging to examine the GM-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…Although we highlighted the findings of mediation analyses for depression and anxiety, across the ASR measures that showed a significant correlation with both total PSQI scores and hypothalamus-rPoCG rsFC, the models of hypothalamus-somatosensory cortical connectivity → sleep disturbance → clinical comorbidities showed significant and complete mediation in most cases ( Supplementary Table S4 ). Note that the findings of mediation analyses do not suggest causality but rather highlight an important role of deficient sleep in inter-relating brain functional changes and emotional symptoms in adults who smoke, as has also been demonstrated for alcohol use disorders ( Zhang et al, 2021b ). These findings suggest that treatments to improve deficient sleep may benefit individuals with nicotine and potentially other substance use disorders.…”
Section: Discussionmentioning
confidence: 80%
“…Although we highlighted the findings of mediation analyses for depression and anxiety, across the ASR measures that showed a significant correlation with both total PSQI scores and hypothalamus-rPoCG rsFC, the models of hypothalamus-somatosensory cortical connectivity → sleep disturbance → clinical comorbidities showed significant and complete mediation in most cases ( Supplementary Table S4 ). Note that the findings of mediation analyses do not suggest causality but rather highlight an important role of deficient sleep in inter-relating brain functional changes and emotional symptoms in adults who smoke, as has also been demonstrated for alcohol use disorders ( Zhang et al, 2021b ). These findings suggest that treatments to improve deficient sleep may benefit individuals with nicotine and potentially other substance use disorders.…”
Section: Discussionmentioning
confidence: 80%
“…Previous work linked possession of ε4 with accelerated age-related cortical thickness loss [ 78 , 79 ]. This itself was associated with self-reported sleep disturbance in healthy community dwelling adults [ 80 ] and reduced objectively measured total sleep time, random eye movement, N2 and N3 stages of sleep in alcohol-use disorder [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on alcohol use disorder patients with sleep disorder showed reduced overall cortical volume (Wiers et al, 2015;Tomasi et al, 2019). Zhang et al (2021) showed that longer sleep-wave and rapid eye movement (REM) sleep was significantly associated with greater cortical thickness. Diffusion tensor imaging showed abnormal inferior frontal gyrus correlations between "SDS" and DTI parameters in ME/CFS patients (Thapaliya et al, 2021).…”
Section: Discussionmentioning
confidence: 99%